PELATIHAN BAHASA INGGRIS BERBASIS DARING DENGAN KONSEP MENTORING DAN TUTOR TEMAN SEBAYA - Fandita Tonyka Maharani (Universitas Majalengka, 2020)
The globalization and disruption era creates effects for the human being; one is the connection between people without boundaries. This thing also brings up the importance of English language usage. This community service was conducted through online English training, which consists of 8 meetings between June-July 2020. The training includes 1 mentor and 3 participants. The initial assessment was conducted to know the participants’ abilities and categorize them into Basic, Intermediate, Advanced classes. This training was categorized in the Basic class. Each meeting was divided into three sessions, which enable the mentor and participants to have conversations with each other. This training uses Conversation Method. The participants were excited, which can be seen by the 87.5 % participatory rate. The final assessment shows an improvement for the participants’ English capability, and they can continue to Intermediate class.